Cytomegalovirus pneumonitis and bone marrow transplantation: identification of a specific high risk group. Issue 5 (May 1993) - Foot, A B; Caul, E O; Roome, A P; Darville, J M; Oakhill, A
Abstract : AIMS–To study the association between cytomegalovirus (CMV) excretion and interstitial pneumonitis in allogeneic bone marrow transplant (BMT) recipients, with reference to donor and recipient CMV antibody response. METHODS–The incidence of CMV excretion was prospectively studied in 62 allogeneic bone marrow transplantations performed on adults and children. All recipients received CMV seronegative blood products. Prophylaxis with high dose acyclovir and CMV immune globulin was given to high risk patients (donor or recipient, or both, CMV seropositive). RESULTS–CMV excretion was detected in eight of 26 (31%) high risk patients but in only one of 36 low risk patients (donor and recipient both CMV seronegative). Five of the eight (63%) excretors in the high risk category developed CMV, of whom four (80%) belonged to the seropositive recipient/seronegative donor group, and included the three CMV seropositive recipients whose CMV complement fixation antibody titres were 64 or greater before transplantation. CONCLUSIONS–These findings suggest that there is a subgroup of patients at especially high risk of developing CMV.